Pressure Selects Dominant Anaerobic Methanotrophic Phylotype and Sulfate Reducing Bacteria in Coastal Marine Lake Grevelingen Sediment - Cassarini, Chiara; Zhang, Yu; Lens, Piet N. L. (Frontiers in Environmental Science, 2019)
Anaerobic oxidation of methane (AOM) coupled to sulfate reduction is mediated by, respectively, anaerobic methanotrophic archaea (ANME) and sulfate reducing bacteria (SRB). When a microbial community from coastal marine Lake Grevelingen sediment, containing ANME-3 as the most abundant type of ANME, was incubated under a pressure gradient (0.1- 40 MPa) for 77 days, ANME-3 was more pressure sensitive than the SRB. ANME-3 activity was higher at lower (0.1, 0.45 MPa) over higher (10, 20 and 40 MPa) CH4 total pressures. Moreover, the sulfur metabolism was shifted upon changing the incubation pressure: only at 0.1 MPa elemental sulfur was detected in a considerable amount and SRB of the Desulfosarcina / Desulfococcus genera were more enriched at elevated pressures than the Desulfobulbus. This study provides evidence that ANME-3 can be constrained at shallow environments (45 m depth), despite the scarce bioavailable energy, because of its pressure sensitivity. Besides, the association between ANME-3 and SRB can be steered by changing solely the incubation pressure. The ANME-3 cells present in the marine Lake Grevelingen possess high specific AOM-SR rates and thus, can be of great potential to be applied in the industry after enrichment.